Group Exhibition-2001/51/EC-Embodied Crossings-Now Boarding - Antoniou, Klitsa (My University, 2026)
2001/51/EC-Embodied Crossings-Now Boarding. Ongoing project/performance. Collaboration with the Museum of Forgetting, Sweden.